Teachers' belief about reading and reading instruction and a redesigned developmental reading course - Viray, Eunice Tablazon (2008)
The study examined the Developmental Reading (DR) teachers' beliefs and practices regarding reading and reading instruction and then developed a new design for the DR course offered in Tertiary Education institutions from the perspective of whole language. The redesigned DR was tried out in the main campus and 9 Extramural Studies Centers of the Palawan State University in the first semester of AY 2003-2004. The instruments included a survey questionnaire and a focus group discussion conducted with the 13 teachers who were to implement the program. Findings show that majority of the respondents believe that teaching reading is difficult, followed by those who viewed it as exciting and enjoyable. It was concluded that the reinvented DR program was effective in enabling the respondents to examine their views and beliefs regarding reading and teaching reading.